A Step-by-Step Sonographic Approach to Vascular Anomalies in the Pediatric Population: A Pictorial Essay - Mittal, Anushka; Anand, Rama; Gauba, Richa; Choudhury, Subhasis Roy; Abbey, Pooja (Indian Journal of Radiology and Imaging, 2021)
Vascular anomalies are a common cause of soft-tissue masses in children and often referred for ultrasonographic (USG) evaluation. They are broadly classified as vascular tumors (hemangiomas, hemangioendotheliomas, and angiosarcomas) or vascular malformations (venous malformations, lymphatic malformations, and arteriovenous malformations). Findings on USG and Doppler imaging can be used to categorize vascular anomalies into high- or low-flow lesions, which forms the basis for further workup, diagnosis, and management. On careful evaluation of various sonographic features, in conjunction with clinical findings, an accurate clinicoradiological diagnosis can be made in most cases. Further imaging with magnetic resonance (MR) imaging or computed tomography (CT) helps in delineation of lesion extent, whereas MR or CT angiography is useful to map the vascular supply of high-flow lesions. We have illustrated and discussed a step-by-step approach to diagnose vascular anomalies using ultrasound and Doppler imaging.
Keywords: arteriovenous malformation; doppler; hemangioma; lymphatic malformation; vascular anomalies; vascular malformations; venous malformation